2011
DOI: 10.1088/2040-8978/13/7/075301
|View full text |Cite
|
Sign up to set email alerts
|

Full control of polarization and temporal shape of ultrashort laser pulses transmitted through an optical fibre

Abstract: We present a method for generating ultrashort pulses of predetermined arbitrary shape at the distal end of a single mode step index fibre. The relevant properties of the fibre—dispersion, birefringence, and onset of non-linearities—are analyzed and included in the shaping procedure. The capabilities of the method are demonstrated with parametrically shaped sub-pulse sequences. In these sequences, each sub-pulse is independently controlled respective to its parameter energy, distance in time, phase, chirp, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…The effects included in this simulation are chromatic dispersion and self-phase modulation (which is the dominating nonlinear effect in the relevant regime). As mentioned in our previous work [12], assuming the dispersion of bulk silica for the simulation leads to systematic differences from the measurement which we attribute to the waveguide dispersion of the fiber. For the simulations presented in this paper we determined experimentally the coefficients β 2 and β 3 in the relevant spectral range (β 1 has no influence on the pulse shape).…”
Section: Simulation and Experimental Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The effects included in this simulation are chromatic dispersion and self-phase modulation (which is the dominating nonlinear effect in the relevant regime). As mentioned in our previous work [12], assuming the dispersion of bulk silica for the simulation leads to systematic differences from the measurement which we attribute to the waveguide dispersion of the fiber. For the simulations presented in this paper we determined experimentally the coefficients β 2 and β 3 in the relevant spectral range (β 1 has no influence on the pulse shape).…”
Section: Simulation and Experimental Resultsmentioning
confidence: 77%
“…It has been shown that for low pulse energies, where the nonlinear effects can be neglected, it is possible to obtain arbitrarily phase-, amplitude-, and polarization-shaped pulses after transmission through a fiber [12]. In this work we demonstrate an approach to obtaining a certain class of phaseshaped pulses after propagation through a step-index fiber in the nonlinear regime, namely pulses that can efficiently and selectively excite two-photon transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Та-кие системы связи основаны на оптических волокнах, которые способны передавать оптические сигналы на большие расстоя-ния. Современные оптические волокна спо-собны передавать последовательности им-пульсов, длительностью порядка 2-8 пс на расстояния от 100 до 1000 км со скоростью от 10 до 12 Гб/с [1]. Однако объёмы переда-ваемой информации растут, и это требует разработки новых методик уплотнения ка-нала связи.…”
Section: Introductionunclassified
“…If nonlinear effects are negligible, a linear dispersion compensating element such as a grating compressor or a pulse shaper is sufficient. However, this is true only for ultrashort pulses with pulse energy of several picojoules [11]. Another possibility is to use photonic crystal fibers that have ei-* monika.pawlowska@fu-berlin.de ther a large mode area [12] or an air-filled core [13,14] and thus a smaller nonlinear parameter.…”
Section: Introductionmentioning
confidence: 99%